Neumonía Tuberculosa. Reporte de 20 casos y estudio caso-control - Gutiérrez C., Jorge (2001)
Tuberculous pneumonia is a special form of pulmonary tuberculosis, inadequate registered in our population and therefore little studied. The present study was made in Service of Medicine of the Hospital Arzobispo Loayza, Lima-Perú, and our goals were to describe the clinical and radiographics characteristics in 20 adult women with tuberculous pneumonia and positive smear, and to establish the differences of greater meaning with a control group of 23 patients with lobar and/or basal bacterial pneumonia. Tuberculous pneumonia was characterized by a mean age of 28 years, duration of symptoms with a mean of 28 days; fever, productive cough and dysnea in all the cases; hiporexia-anorexy in 95%, thoracic pain in 50%, hemoptisis in 15%, tuberculous contact in 60%, condensation syndrome with or without pleural effusion 75%, and in the lower lung field in 80%, other radiographics findings that accompanied the lung consolidation in 70%, leukocytosis in 65%, ESR between 49 and 58 mm/h and hipoxemia of some degree in 100% of the cases. We conclude, tuberculous pneumonia in our population is a predominant disease of subjects of 35% years or less, with a time of duration of symptoms of 4 weeks and the commonest localization is the low lung field; the characteristics that allos to differentiate it from lobar and/or basal bacterial pneumonia are the duration of symtoms greater 15 days, with nonpleuritic pain or absent, anorexy, weight loss, anemia,tuberculous contact, radiographics finding that accompany the lung consolidation as the infiltrated presence by apical, granulia and bronchogenic dissemination, the outcome is slower the specific therapy and the hospital stay more prolonged.